2019
DOI: 10.1007/s12195-019-00579-y
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of 3D Printed Stretching Devices for Imaging Force Transmission in Live-Cells

Abstract: Introduction-Cell stretch is a method which can rapidly apply mechanical force through cell-matrix and cell-cell adhesions and can be utilized to better understand underlying biophysical questions related to intracellular force transmission and mechanotransduction. Methods-3D printable stretching devices suitable for livecell fluorescent imaging were designed using finite element modeling and validated experimentally. These devices were then used along with FRET based nesprin-2G force sensitive biosensors as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 23 publications
3
18
0
Order By: Relevance
“…Previous studies have shown that mechanical stretching leads to changes in nuclear shape and size ( Anno et al, 2012 ; Brosig et al, 2010 ; Hoffman et al, 2020 ; Mayer et al, 2019 ). To verify that our stretcher could be used to study the impact of stretching on cells, we subjected U2OS cells to incremental static stretch and measured changes in nuclear area.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that mechanical stretching leads to changes in nuclear shape and size ( Anno et al, 2012 ; Brosig et al, 2010 ; Hoffman et al, 2020 ; Mayer et al, 2019 ). To verify that our stretcher could be used to study the impact of stretching on cells, we subjected U2OS cells to incremental static stretch and measured changes in nuclear area.…”
Section: Resultsmentioning
confidence: 99%
“…Some are commercially available (Flexcell, Strex, Electron Microscope Sciences, etc. ; Callaghan and Williams, 2000 ; Matsugaki, Fujiwara, and Nakano, 2013 ; Richard et al, 2007 ), and many labs have designed and built their own custom stretchers ( Boulter et al, 2020 ; Daulagala et al, 2020 ; Huang and Nam-Trung, 2013 ; Huang et al, 2010 ; Isermann et al, 2012 ; Mayer et al, 2019 ; Roth et al, 2015 ; Shiwarski et al, 2020 ). Our system contributes to this line-up of stretchers in that it has a very simple design, with easy adaptation to experimental needs, and relatively low cost of entry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, to confirm whether interactions between nesprins and SUNs are required for the formation of proper nucleolar morphology, we used a dominant‐negative KASH construct (DN‐KASH, Mayer et al, 2019). Expression of DN‐KASH altered the morphology of the nucleoli and severely decreased the intensity of nucleolin staining compared with untransfected cells in the same field (Figure 3g, arrows indicate transfected cells), demonstrating that the interactions between nesprins and SUNs are indeed required for the determination of nucleolar structure.…”
Section: Resultsmentioning
confidence: 99%
“…pEGFPN3‐SUN1_888 and pEGFPN3‐SUN1_916 have been previously described (Nishioka et al, 2016). An expression vector for dominant‐negative KASH (DN‐KASH)‐mCherry fusion protein was a gift from Daniel Conway (Virginia Commonwealth University, Addgene plasmid #125553) (Mayer et al, 2019). Expression plasmids for myc‐tagged mouse SUN1_913 and GFP‐tagged SUN1_888(mut) were from OriGene (Rockville, MD, USA) and VectorBuilder, Japan (Kanagawa, Japan), respectively.…”
Section: Methodsmentioning
confidence: 99%